The long conversation : maximizing business value from information technology investment - Lorenzo, Oswaldo; Kawalek, Peter; Gonzalez, Gaston; Ramdani, Boumediene (Basingstoke, UK : Palgrave Macmillan, 2011)
"For the last 20 years, companies have been adopting and implementing large-scale information systems, providing the backbone of many organizations worldwide. The implementation of these platforms has to be carried out with clear strategic and operational aims: to automate transactions, reduce costs, increase customer satisfaction, integrate with suppliers, and ultimately make better decisions. And yet, companies find this experience to be not as easy as they initially anticipate. Projects are harder, business cases are more difficult, and the learning process is much, much longer. Why is this happening? And what do firms do to ensure that they get value from their investment in technology? The reality is that it takes a long time and a lot of learning to get the best out of your IT systems. What businesses really need now is to stop looking for the next technology silver bullet and make the most of what they already have. In short, businesses need to maximize the value of their existing IT assets. To succeed in the coming years, companies must continue and intensify what these authors call 'The Long Conversation' - the strategic and operational dialogues that businesses began years ago. Companies do not need to reach first for new hardware and/or software, but they do need new organizational practices, new capabilities and new social networks to support the continuity of that conversation."--Publisher's website
Includes bibliographical references and index
Keywords: Information technology -- Management; Information technology -- Economic aspects